Performance Comparison Of Shunt Rf Mems Switches (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This is an attempt to compare three different shunt configured RF MEMS switches which offers a choice for applications in satellite and antennas. Advanced RF communication domain demands for design and modeling of RF MEMS switch which provides extremely reduced pull-in voltage, better isolation, low insertion loss, and with greater reliability. The proposed work manages with comparison of design modeling and performance of three different shunt configured RF MEMS switches. The proposed shunt configured RF MEMS switches are designed with different dimensions with different meandering techniques with perforations on beam structure helps in reducing the amount of voltage required for actuation of switch which is known as pull-in voltage. Comparative study of three different RF MEMS switches which involves in conducting electromechanical analysis are carried out using COMSOL multi physics tool and electromagnetic analysis are carried out using HFSS tool. Moreover the comparative study involves in comparing the values of pull-in voltage, switching time and capacitance, stress, insertion loss, return loss and isolation of three different RF MEMS switches. Proposed first switch model derives pull-in voltage of 16.9v with the switching time of 1.2µs, isolation of 47.70 dB at 5GHz and insertion loss of 0.0865 dB and return loss of 41.55 dB. Proposed second switch model derives pull-in voltage of 18.5v with the switching time of 2.5µs, isolation of 37.20 dB at 8GHz and insertion loss of 0.1177 dB and return loss of 38.60 dB. Proposed third switch model delivers pull-in voltage of 18.75v with the switching time of 2.56µs, isolation of 44.1552 dB at 8GHz and insertion loss of 0.0985 dB and return loss of 42.1004 dB.